The experience of endovascular treatment of brain arterial aneurisms using stent-systems and supplementary balloon-catheter technique - Cherednichenko, Yu. V.; Zorin, N. A.; Miroshnichenko, A. Yu. (Ukrainian Neurosurgical Journal, 2009)
The experience of brain arterial aneurisms endovascular treatment using stent-systems and supplementary balloon-catheter technique is described. 204 endovascular operations for aneurisms exclusion were performed, 14 of them — using the above mentioned methods. Clinical and anatomical peculiarities of aneurisms, which require application of balloon- and stent-assistant technique, as well as aneurisms exclusion using isolative stents are described.